2001
DOI: 10.1002/pam.2026
|View full text |Cite
|
Sign up to set email alerts
|

Cases and Controversies: How Novitiates Are Trained to Be Masters of the Public Policy Universe

Abstract: Public policy schools were established 30 years ago to provide analytic and management skills to aspiring policy professionals. A centerpiece of policy management training has been the action-centered teaching case, modeled after the cases long used in business schools. Though other aspects of public management teaching and research have been vigorously debated, little attention has been paid to the content of teaching cases.Taking these texts as a central element in policy student socialization, the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…The case protagonists are the characters with whom readers most readily identify and whose roles are adopted by students during class discussion (Chetkovich/Kirp 2001). The choice of case protagonists is important because it is through this that organizational "reality" is presented in teaching cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The case protagonists are the characters with whom readers most readily identify and whose roles are adopted by students during class discussion (Chetkovich/Kirp 2001). The choice of case protagonists is important because it is through this that organizational "reality" is presented in teaching cases.…”
Section: Resultsmentioning
confidence: 99%
“…Chetkovich and Kirp (2001) studied the ten best-selling public policy cases in the Kennedy School of Government at Harvard University. They found that those tended to feature high-level, lone protagonists beset by hostile political forces.…”
Section: Naive Politicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is unsurprising given that for many management teachers and students the primary purpose of a teaching case is to provide the opportunity to identify with management and to make a managerial decision (Chetkovich and Kirp, 2001;Lundberg et al, 2001;Liang and Wang, 2004).…”
Section: Teaching Cases Privilege Senior Management's Viewsmentioning
confidence: 96%
“…In his seminal piece on the policy sciences, Lasswell (1951) built on Charles Merriam's work, which emphasized ''breaking down barriers that separate scholars from one another, and of leveling-up methodological competence everywhere.'' Early policy sciences practitioners were ''intellectual border-crossers'' (Chetkovich and Kirp 2001), and their vision was for policy to combine diverse disciplines in a quest to find better responses to policy issues with a strongly democratic focus. Lasswell (1951) recognized that context is key and that our most powerful and creative results arise when we ''unify quantitative and nonquantitative observations and point the way to new empirical, theoretical, and policy activities.''…”
Section: Introductionmentioning
confidence: 99%